NEED ASSESMENT UNTUK PROGRAM PENYULUHAN PERKOPERASIAN PADA KOPERASI “WARGA SAUYUNAN” KAMPUNG NAGA, KABUPATEN TASIKMALAYA - Wawan Lulus Setiawan (Jurnal Co Management, 2019)
The "warga Sauyunan " cooperative in Kampung Naga as well as cooperatives in Indonesia generally has a very important role in the economy of the community. This cooperative serves local residents to purchase daily consumption needs and savings and loans. This cooperative is unique because of the existence of this cooperative in the environment of an indigenous community that still maintains strong traditions. However, this cooperative faces the problem of the limited competency of cooperative human resources (which includes the board of cooperatives and members of cooperatives) on the aspects of cooperatives values and the management of cooperatives. Therefore, one of the urgent efforts made by the cooperative is conducting cooperative counseling, both for staffs and members of cooperatives. Based on this background, a "need assessment" was conducted for the preparation of cooperative education programs for managers and members of the Warga Sauyunan ' cooperative. This activity as an effort to help the Warga Sauyunan Cooperative develop a cooperative education program needed to improve the quality of human resources in the Warga Sauyunan Cooperative.